A Comparison of the Expected and Performed Roles of the Geotourism Stakeholders at Hummanaya, Sri Lanka: https://doi.org/10.36777/jag2023.2.2.9 (Journal of Asian Geography, 2023)
Geotourism is a niche market that sells the geographic uniqueness of places, and Hummanaya is one such destination. Geotourism stakeholders are agents who shape, positively or negatively, the geographical characteristics of a place. They have three key roles to play to sustain and even enhance the geotourism allure of a destination and the well-being of its residents. Those roles are programming, facilitating, and gatekeeping. The Special Area Management Plan (SAMP) has suggested several strategies and management actions for the stakeholders to implement in Hummanaya, one of the geotourism destinations in Southern Sri Lanka, to sustainably develop the area while mitigating the socio-cultural, economic, and environmental issues in the area. The primary objectives of the research were to identify the geotourism stakeholders of the Hummanaya destination and to examine the extent to which the stakeholders have fulfilled the responsibilities suggested by the SAMP and other literature over the past two decades. Key informant interviews and observation methods were conducted to collect data and information. Seventy-seven key informants were involved in key informant interviews. State-centric stakeholders were identified as having played programming and facilitating roles to some extent but neglected the gatekeeping role. The local community is not fully committed to sustainably programming the ecotourism activities and gatekeeping activities in the destination and facilitating them for tourists, even though some facilities are provided. Also, they have not become the custodians of the destination. Thus, to make Hummanaya a sustainable tourism destination, this study recommends that each stakeholder should pay enough attention to fulfil all three roles.